Efektivitas Nipple Puller pada Puting Flat Ibu Postpartum Sectio Caesarea: Studi Kasus: Nina Sunarti, Wanda Diasti Ningrum, Joao Manuel Correia Ximenes - Nina Sunarti; Wanda Diasti Ningrum; Joao Manuel Correia Ximenes (STIKes Persada Husada Indonesia, 2026)
Post sectio mothers face greater breastfeeding obstacles than normal delivery, this occurs due to surgical pain, limited mobility, difficulty in breastfeeding positions, delays in early breastfeeding initiation can worsen the condition of flat nipples. This condition can interfere with the success of exclusive breastfeeding. The purpose of the study was to evaluate the effectiveness of nipple puller exercises in improving nipple eversion and the quality of breastfeeding attachment in postpartum sectio caesarean mothers with flat nipples. The research design used a case study with a nonpharmacological intervention-based approach to maternity nursing care conducted prospectively to evaluate the effectiveness of nipple puller exercises using the modified syringe method according to standard procedures, which were performed on three postpartum mothers on days 1 - 4 of the year for 2–3 times a day in 4 days of treatment. Data collection methods included interviews, direct observations, documentation of nipple shape changes, attachment success and effective breastfeeding ability. Evaluation was carried out through observation of changes in putting conditions, the success of baby attachment, the ability of the baby to breastfeed effectively, and the comfort of the mother while breastfeeding. The results showed that all three patients experienced significant improvements in nipple eversion and improvement in attachment quality after consistent Nipple Puller exercises. All mothers reported increased breastfeeding comfort and reduced barriers in the lactation process. Changes are characterized by the appearance of adequate nipple protrusion and an improvement in the quality of the baby's attachment, characterized by effective suction, the absence of significant pain in the mother, and a reduced incidence of detachment of attachment during breastfeeding. In conclusion, the Nipple Puller (Syringe Method) exercise is effective as a simple, safe, cheap and easy-to-apply intervention to help overcome flat nipples in postpartum caesarean section mothers in supporting the success of lactation, so it has the potential to be recommended in the practice of lactation services in health facilities.